2000
DOI: 10.1002/1097-0142(20000815)89:4<750::aid-cncr5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of gemcitabine in patients with advanced hepatocellular carcinoma

Abstract: BACKGROUND The objective of this study was to evaluate the efficacy and toxicity of gemcitabine in patients with chemotherapy‐naïve, advanced hepatocellular carcinoma (HCC). METHODS Twenty‐eight patients with unresectable and nonembolizable HCC who had received no prior systemic chemotherapy and with objectively measurable tumors, adequate liver and renal function, and adequate bone marrow reserve were enrolled on this study. The therapy consisted of gemcitabine 1250 mg/m2 intravenously over 30 minutes weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 19 publications
2
83
0
5
Order By: Relevance
“…Many small-scale trials of combining MTT with cytotoxic chemotherapy have been reported [385][386][387][388][389]. However, the treatment efficacy in terms of tumor response rate and patient survival were similar to those reported for the cytotoxic regimens alone (Table 3) [372,[375][376][377][378][379][380][381][382]. A second approach is to combine MTT targeting different molecular pathways.…”
Section: Future Directionsmentioning
confidence: 83%
See 1 more Smart Citation
“…Many small-scale trials of combining MTT with cytotoxic chemotherapy have been reported [385][386][387][388][389]. However, the treatment efficacy in terms of tumor response rate and patient survival were similar to those reported for the cytotoxic regimens alone (Table 3) [372,[375][376][377][378][379][380][381][382]. A second approach is to combine MTT targeting different molecular pathways.…”
Section: Future Directionsmentioning
confidence: 83%
“…However, 25% of patients died of doxorubicin-related complications, including infection and cardiotoxicity. The antitumor activity of newer cytotoxic agents, such as gemcitabine [378,379], oxaliplatin [380], and capecitabine [381], has been modest, with single-agent tumor response rate of 10% or less ( Table 2). The most common grade 3-4 toxicity was myelosuppression, which occurred in 10-40% of the patients.…”
Section: Cytotoxic Therapy: Single Agent and Combinationmentioning
confidence: 99%
“…Therefore, based on pre-clinical rationale gemcitabine was evaluated in patients with advanced HCC. In a phase II study of gemcitabine in treatment-naive patients with advanced HCC, 5 patients (18%) had objective responses with mild toxicities (17). However, two subsequent phase II studies of gemcitabine failed to show meaningful clinical efficacy [0-5% overall response rate (ORR)] (18,19).…”
Section: Gemcitabinementioning
confidence: 99%
“…Notably, 25% of patients died due to doxorubicinrelated complications, including septicemia and cardiotoxicity. The antitumor activity of other cytotoxic agents such as gemcitabine [62,63] , oxaliplatin [64] , and capecitabine [65] in clinical and retrospective studies was modest with objective responses of < 20%. In randomized controlled trials, combination therapies such as PIAF (cisplatin, interferon, adriamycin, fluorouracil) and FOLFOX (5-fluorouracil, folic acid, and oxaliplatin) did not significantly improve survival compared with doxorubicin [59,60] .…”
Section: Medical Therapiesmentioning
confidence: 99%